Fiscal Decentralization Policies in the EU: A Comparative Analysis through a Club Convergence Analysis. Issue 3 (3rd May 2020) - Blanco, Francisco; Delgado, Francisco J.; Presno, Maria J.
Abstract: We study the degree of convergence or divergence in fiscal decentralization in the European Union over the period 1995–2015 using a club convergence approach. First, we analyze non-central expenditure and revenue as percentages of GDP, of total expenditure and of total revenue. The results for the EU-15 countries indicate some clustering, with three clubs formed when using GDP and four to five when using total revenue or expenditure. Second, we study the gap between expenditure and revenue as a proxy of fiscal responsibility. This results in three and two clubs respectively, with Denmark as the divergent country with the highest gap. Finally, we analyze potential unions of clubs and transitions. We also interpret our results taking into account variables found in the literature as determinants of fiscal decentralization. These results show how European countries are quite heterogeneous in terms of fiscal federalism and decentralization, with greater convergence in fiscal responsibility than in the other magnitudes.